THE TERATOGENIC EFFECTS OF RETINOIC ACID ON EPITHELIORETICULAR CELLS AND HASSALL'S CORPUSCLES IN THE MEDULLA OF THE CHICK THYMUS: Retinoic Acid on Epithelioreticular Cells And Hassall's Corpuscles - Haque, Ayesha; Yunus Khan, Muhammad (Pakistan Armed Forces Medical Journal, 2017)
Objective: To examine the effects of prenatal administration of retinoic acid on the proliferation of epithelioreticular cells and Hassall's corpuscles in the medulla of chick thymus.Study Design: Experimental study.Place and Duration of Study: Anatomy Department, College of Physicians and Surgeons Pakistan (CPSP) Regional centre, Islamabad, from February 2009 to February 2010.Materials and Methods: A total of 120, fertilized chicken eggs were divided into an experimental group A, and its control group B. Group A was injected with retinoic acid via yolk sac on day zero of incubation. Group B was sham injected with saline. Subgroup A1 and B1 were incubated till embryonic day 15 and subgroups A2 and B2 were incubated till hatching. The number of epithelioreticular cells and Hassall's corpuscles were counted. Diameter of Hassall's corpuscles was measured. The parameters were compared statistically between the experimental and control groups.Results: The number of epithelioreticular cells was significantly less than the control group at embryonic stage (p=0.009) as well as at hatching (p=0.001). The number of Hassall's corpuscles was not different between the embryonic groups but was considerably more than the control in the experimental group at hatching (p=0.01). The diameter of the Hassall's corpuscles belonging to the experimental groups was significantly different than the age matched control groups at the embryonic stage (p=0.004) as well as at hatching (p=0.008).Conclusion: Prenatal exposure to retinoic acid significantly reduced the number of epithelioreticular cells and increased the size and the number of the Hassall's corpuscles.